A SPATIAL AND TEMPORAL ANALYSIS OF LAND USE CHANGES IN TWO MOUNTAIN VALLEYS: WITH AND WITHOUT DAM RESERVOIR (POLISH CARPATHIANS) - Wiejaczka, Łukasz; Olędzki, Jan Romuald; Bucała-Hrabia, Anna; Kijowska-Strugała, Małgorzata (Quaestiones Geographicae, 2017)
This study analyzed the temporal and spatial changes in land use taking place in two adjacent river valleys, located within the Polish Carpathians. The land use in 1977 and 2009 was presented for selected areas. In one of the valleys, a dam has been operating since 1994 along with a retention reservoir, which is an additional factor influencing the direction and scale of the land use changes. An analysis using GIS techniques showed that the general directions of transformation in both valleys in the land use structure are similar but with different intensity. In studied valleys a decrease of area with agricultural land and gradual increase in the forested area have been observed. In the valley with the reservoir few more changes were noticed. The decrease of the forested area by 5.5% and farmland by 8.2% on the areas submerged by reservoir was observed. The strip fields pattern has been changed into more dispersed. The road network development was also observed, as well as the change of nature of residential/agricultural buildings into residential/recreational.